Representa????es sociais do crack por usu??rios em situa????o de rua - Quint??o, Ingrid Pereira (2017)
The study evidences the social representations of street crack users, in order to identify the meanings that this portion of the population individually dispenses with drug use. This study was carried out in two spaces of agglomeration of users of psychoactive substances in the center of Bras??lia and Gama, administrative region of the Federal District, with five people interviewed, four men and one woman. The analysis of the data pointed to representations that arose in a paradoxical way, in a contradictory non-excluding perspective. Thus, the categories discussed: The paradoxical representation of crack use, The complex representation of identity and The paradoxical permanence of crack use, revealed that drug users organize their representations anchored in the social imaginary that the use of crack refers to the disease and Delinquency, but they objectify their experiences in a singular way, confirming a transgressive function to the hygienist and criminalizing place that the society destines them. Insofar as they do not disregard the obvious harms of drug use, they identify functions of use such as life, well, relief and independence, which provide a greater understanding of the identity construction of crack users in street situations. The results show that in the context of the exclusion that the subjeComunidades Terap??uticas are subjected, with policies, that do not embrace the paradoxical and complex dimension that packs the dynamics of drug use, like the one adopted by the current S??o Paulo government, the search for "the next stone of Crack "becomes a dynamic imprisonment of permanence of use, that does not allow reaching of the desired identity place, that of subjeComunidades Terap??uticas of rights.